Screening Antibacterial Activity in Soft Coral Extract Sinularia sp. from Pahawang Island Waters, Lampung - Anma Hari Kusuma; Muhammad Gilang Arindra Putra; Oktora Susanti; Rachmad Caesario; David Julian; Andre Vanbudi (Journal of Fish Health, 2026)
Sinularia sp. is one of the most widespread and abundant types of soft coral in Indonesian waters. The soft coral Sinularia sp. haves many bioactive compounds to use as a patogen antibacterial agent. The aim of this research was to compare the antibacterial activity from the soft coral Sinularia sp. against the pathogenic bacterial strain Escherichia coli. Samples of the soft coral Sinularia sp. were collected by SCUBA diving equipment at around Pahawang Island, Pesawaran Regency, Lampung, Indonesia, in July 2025. In this study, two species of soft corals, Sinularia polydactyla and Sinularia flexibilis, were found at the research site. The extract yields for soft coral species used methanol resulted in higher values compared to ethyl acetate and hexane. The antibacterial activity of the extract soft corals against the pathogenic bacteria E. coli used ethyl acetate solvent better than methanol and hexane. Soft coral extract for Sinularia sp. with ethyl acetate solvent can be used as antibacterial candidates against the pathogenic bacteria E. coli.